Pemberdayaan Usaha Kecil Mikro Menengah Melalui Platform Digital di Desa Kujang Oleh Dinas Koperasi Usaha Kecil Menengah dan Perdagangan Kabupaten Ciamis - Fahrezi, Akmal Maulana; Munir, Sirodjul; Yuliani, Dini (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by problems in the implementation of the strategy of the Ciamis Regency Small and Medium Business Cooperative Office in the development of Micro and Medium Small Enterprises in Kujang Village, Cikoneng District, Ciamis Regency. The method used in this study is descriptive with a causative approach. Primary data is sourced from the results of interviews with 6 selected informants who are relevant to the problem. Secondary data is sourced from documents, books, journals, reports, and legislation. Data collection was carried out based on interviews, observations, and documentation with data analysis techniques through data reduction, data triangulation, and conclusion drawn. The results of the study show that the MSME development strategy through digital platforms has not been running optimally. Obstacles occur in the lack of communication, active participation of MSME actors in policy formulation, mentoring activities, facilitation, evaluation, and programs that are still top-down. Efforts to overcome obstacles are to increase the initiative of MSME actors in learning independently through digital media such as YouTube, and TikTok through e-commerce. The Kujang village government supports the implementation of training and facilitation if it is involved by the relevant agencies. The Cooperative Office, Small and Medium Enterprises and Trade is improving its strategy through further collaboration with village governments that have not received attention, especially Kujang village MSMEs in participating, mentoring, coaching, and facilitating.